Libraries: a definition from another context - Sánchez Espinoza, Florybeth (2010)
This essay presents a series of reflections that revolve around the discipline of librarianship and the professionals who are trained in it. It encompasses the concept of librarianship from the formal point of view, provided by some authors and dictionaries, but also from the very particular vision of the author, who conceptualizes it from the working level, academia, research and daily contact with users. Therefore, it is a brief journey from the traditional conception to the current reality, with the inclusion of information and communication technologies. But above all, it is a journey of a very personal feeling.